Chemokine receptor CXCR2 in primary sensory neurons of trigeminal ganglion mediates orofacial itch - Li, Dong-Jin; Zhong, Zhen-Juan; Wang, Xiao-Liang; Wei, Na; Zhao, Si-Jia; Shan, Ting-Ting; Liu, Ya-Ping; Yu, Yao-Qing (Frontiers in Molecular Neuroscience, 2023)
The CXCR2 chemokine receptor is known to have a significant impact on the initiation and control of inflammatory processes. However, its specific involvement in the sensation of itch is not yet fully understood. In this study, we aimed to elucidate the function of CXCR2 in the trigeminal ganglion (TG) by utilizing orofacial itch models induced by incision, chloroquine (CQ), and histamine. Our results revealed a significant up-regulation of CXCR2 mRNA and protein expressions in the primary sensory neurons of TG in response to itch stimuli. The CXCR2 inhibitor SB225002 resulted in notable decrease in CXCR2 protein expression and reduction in scratch behaviors. Distal infraorbital nerve (DION) microinjection of a specific shRNA virus inhibited CXCR2 expression in TG neurons and reversed itch behaviors. Additionally, the administration of the PI3K inhibitor LY294002 resulted in a decrease in the expressions of p-Akt, Akt, and CXCR2 in TG neurons, thereby mitigating pruritic behaviors. Collectively, we report that CXCR2 in the primary sensory neurons of trigeminal ganglion contributes to orofacial itch through the PI3K/Akt signaling pathway. These observations highlight the potential of molecules involved in the regulation of CXCR2 as viable therapeutic targets for the treatment of itch.